PREFACE VOL. 14 NO. 3 (DESEMBER) - Surtiati, Rahayu (UI Scholars Hub, 2024)
In the December 2024 edition, Paradigma presents ten articles covering four regions: Surakarta, Southeast Sulawesi, Minangkabau, Ponorogo; and also areas: cinema, dance, language, fashion, and education. All research are about cultures in Indonesia and written by Indonesian researchers. This open journal is read by the international public, so we hope that humanities researchers in various regions of the world will participate with their writing, not only reporting research in Indonesia, but also research in other regions of the world. Paradigma is preparing to become an international journal and in time its triannual publications will be in English so that more international articles can be published. We thank the article contributors who have developed this journal so that the citation rate is quite high. In addition, we really appreciate the reviewers who faithfully and critically review the article manuscripts. We do not forget to express our gratitude to the language editors, both Indonesian and English, who carefully improved the language quality of this journal. Merry Christmas and a Happy New Year 2025.